Islamic Multicultural Education Innovation Through Transformational Leadership: An Analysis of the Cadre Model at the Pondok Modern Darussalam Gontor - Hajar, Aprilita; Maskuri, Maskuri; Anwar, Chairil (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
Regeneration of leadership that is less structured in some boarding schools is a challenge in maintaining the quality of the institution. One of the main factors contributing to this problem is the weak regeneration system. This study aims to analyze the application of transformative leadership in the regeneration system in Pondok Modern Darussalam Gontor and its impact on the development of multicultural Islamic education. This study uses a descriptive qualitative approach to data collection techniques through the study of literature and analysis of regeneration systems and educational innovation in Gontor. The results showed that transformative leadership in Gontor was able to integrate Islamic values with a modern multicultural-based approach. The regeneration Model applied includes value and character education, habituation, santri organization system, and sustainable leadership training. This transformative leadership contributes to the development of Islamic education that is innovative, inclusive, and relevant to global demands. The implications of this study indicate that the success of the regeneration system in Gontor plays a role in maintaining the existence of the institution for almost a century and producing alumni who take part in various fields, including politics, education, and social. The study provides an academic contribution in understanding the role of transformative leadership in Islamic education as well as offering recommendations for other Islamic educational institutions in adapting the model of regeneration as a strategy to ensure continuity of leadership and maintain the relevance of education in the modern era.